Efeito do Butirato na resposta de células gliais entéricas às toxinas do Clostridioides difficile - Sousa, Arkila Pinheiro Rodrigues de (2024)
C. difficile is the main cause of nosocomial diarrhea worldwide. Enteric glia, a cellular component of the enteric nervous system, are susceptible to C. difficile toxins A (TcdA) and B (TcdB), which are the main virulence factor related to the disease. Microbiota play an important role on susceptibility to C. difficile infection (CDI). One of the products of the microbiota is butyrate, which has been shown to be protective against CDI. In this study, we evaluated whether butyrate could modulate the response of enteric glia to C. difficile toxins. In vitro, rat enteric glia line was incubated with TcdA or TcdB alone or in combination with sodium butyrate 1h prior to toxins challenge. After 18h incubation, enteric glia was collected to analyze cell death (by using a RealTime-Glo annexin and caspase 3/7 activity assays) and levels and expression of bcl2 (an antiapoptotic factor), S100B and IL-6 by qPCR. C. difficile toxins (TcdA and TcdB) induced enteric glia death followed by increased levels of caspase 3/7 and downregulation of bcl2, as well as upregulated the expression of pro-inflammatory mediators (S100B and IL-6). In high concentration, butyrate (200 μM) potentialized the effects of C. difficile toxins in promoting enteric glia death, as shown by increased levels of phosphatidylserine-annexin V binding (TcdA: p = 0.0001, TcdB: p= 0.01) and caspase 3/7 activity (p<0.0001). Whereas low concentration of butyrate (0.2 μM) decreased enteric glia death (TcdA: p = 0.0004, TcdB: p= 0.02) and their caspase 3/7 activity (p<0.001) induced by C. difficile toxins. In addition, low concentration of butyrate (0.2 μM) by itself upregulated bcl2 expression compared to control cells (p<0,0001), as well as decreased the downregulation of bcl2 (p<0.02) and upregulation of IL-6 (p<0.0002) induced by TcdB. Further, low concentration of butyrate (0.2 μM) also diminished S100B upregulation induced by TcdA (p=0.04). Our findings suggest that low and high concentration of butyrate can differentially affect the susceptibility of enteric glia to C. difficile toxins, being the low concentration protective against the deleterious effects of C. difficile toxins, decreasing the enteric glia death by decreasing caspase 3/7 activity and increasing the antiapoptotic mediator (bcl2), as well as reducing the proinflammatory response of these cells. Thus, these findings, in part, brought new perspectives on how microbiota-derived products can modulate the response of enteric glia to the C. difficile toxins.